Borja Reis, discurso e imprensa: estratégias discursivas empregadas em O Progresso/Diário Dos Campos em Ponta Grossa-PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
This work was carried out with the purpose of studying the speech of the journalist Hugo Mendes de Borja Reis, in the newspaper O Progresso. The newspaper was constituted as a primary source and our access to the material was by digital means. We analyzed, with tools of French Speech Analysis trends, how the press was conceived and defended by this journalist. We worked with written texts from 1909 to 1914. The main theorists who founded the analysis were Dominique Maingueneau (1997, 2008) and Authier-Revuz (1998). We sought to understand the conceptions about the press of the journalist who lived in the early twentieth century and how the construction of his discursive ethos took place. The newspaper was founded in Ponta Grossa, Paraná.
Keywords: Imprensa; Análise do Discurso; História; Press; Discourse Analysis; History; CNPQ::LINGUISTICA, LETRAS E ARTES